“Just The Way You Are”: Self-Compassion, Community Social Support & Self-Acceptance of Parents With Down Syndrome Children - Sovi Septania; Vicilia Ridhowati (Guidena)
Abstract Parents with down syndrome children often experience difficulties with self-acceptance of their child’s special needs. Parents cover up the child’s condition from society, alienate the child from social activities, do not facilitate with required therapy, and eventually impact general parenting given. Parents who moved by child need to open up to join a community with other parents with down syndrome children as a necessity for social support. Internally, parents who can accept the weaknesses and strengths of their children are one the characteristics of self-compassion. This study aims to analyze the impact of self-compassion and community social support on parents’ self-acceptance. Using quantitative research methods with Likert scales consists of all instruments (self-compassion, community social support, and self-acceptance scale). They are analyzed with multiple regression techniques and purposive sampling with 50 respondents involved. The results showed that self-compassion and community social support contribute to the self-acceptance of parents with down syndrome children by 52.8 % (p<0.01). Separately, community social support had a 39.9% impact, while self-compassion had a 43.9% impact on the self-acceptance of parents with down syndrome children.